Pengaruh Pendekatan Inkuiri Terbimbing dipadu dengan Diagram Alir terhadap Prestasi Belajar Siswa SMA - PAHRIAH, PAHRIAH (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2015)
This study aims to compare student achievement in teaching chemical equilibrium topics using a guided inquiry approach combined with and without flow charts. This research is a quasi-experimental study with a pretest-posttest control group design. The study sample consisted of 31 experimental class students and 24 control class students. The instruments in this study consisted of two types, namely (1) the instrument of treatment in the form of learning devices using a guided inquiry approach combined with flow diagrams in the experimental class students and guided inquiry learning in control class students, while (2) measurement instruments in the form of learning outcomes tests students, student activeness observation sheets, and student performance assessment sheets. The instruments are declared valid by 2 chemistry lecturers and 1 chemistry teacher who has good competence and experience in chemistry and chemistry learning. The results showed that the guided inquiry approach combined with the flow diagram provided students’ cognitive learning achievements (83.87 experimental classes and 70.83 control classes), affective (79.00 experimental classes and 74.00 control classes), and psychomotor (84.00 experimental class and 80.00 control class) were better than guided inquiry approaches without flow diagrams.